UPAYA PEMBANGUNAN KARAKTER MAHASISWA STAIN PEKALONGAN MELALUI KEGIATAN MENULIS KARYA ILMIAH BERPRINSIP ESQ 165 (SATU IHSAN, ENAM RUKUN IMAN, DAN LIMA RUKUN ISLAM) - Fauzan, Muchamad (IAIN Pekalongan, 2012)
Like the university as a front line in developing human potential students to become superior both academically and character, it would require the development of curriculum that can support the achievement of these goals. One is the development of character-based learning or lectures. Therefore, in this paper offer a principled method of writing scientific papers ESQ 165, which is a method of writing scientific papers involving spiritual development of emotional intelligence (ESQ) the author with the insertion and integration of values ESQ 165. In the early stages, this method has been implemented in Indonesian lectures at STAIN Pekalongan.